A comparative model of party-states: the structural reasons behind similarities and differences in self-reproduction, reforms and transformation - Maria Csanadi (Hungarian Academy of Sciences, Institute of Economics, 2004)
This paper draws up an empirically based comparative analytical model called by its constructor as the Interactive party-state model (IPS). It details the elements, the principles of connection of these elements and the principle of operation of the whole party-state construct. It also defines the specific principles of operation based on the characteristics of the structure, the specific motivations and behavior deriving from those. The model reveals the structural reasons of the differences in power distribution and describes how these structural differences imply different frequency of meeting structural constraints for reproduction, different time-span for recreating cohesion and different means of resource acquisition for selfreproduction, leading to different paths of development and transformation. The IPS model points to the consequences of these different dynamics on the location, pace, sequence of reforms and the regime these reforms occur.
Keywords: 330; party-states; comparative model; transformation; soft budget constraints; reforms; decentralization; disintegration